Relations entre prosodie et syntaxe - Sophie Herment (Anglophonia)
This paper addresses the question of the interface between prosody and syntax through the analysis of a few non canonical syntactic structures taken from corpora of spoken English. It-clefts, extrapositions, right noun-phrase dislocations and the insertion of auxiliary do in an assertive context are closely looked at. The prosody of these structures is compared to marked prosodic forms of emphatic utterances with a neutral syntax. The prosodic analysis is mainly based on the number of tone units, the place of the nuclear syllable and the pitch movement. The context and the information structure are also taken into account for the utterances analysed here. We show that a syntactically non canonical utterance can be pronounced with a neutral prosody or on the contrary that the prosody can be marked. Prosody and syntax are complementary but play a role at different levels. It is argued that a non neutral syntax is rather used for the organization of discourse, for thematization or focalisation, while prosody is used to emphasize an element or highlight a contrast when it is non neutral, and plays a role on the pragmatic or semantic level when it is neutral.